THE ROLE OF INNOVATIVE COMPONENT IN THE DEVELOPMENT OF REGIONAL ECONOMIC POLICY IN MODERN CONDITIONS - O. Solntseva; P. Fedorova (Вестник университета)
The arguments of necessity of the development innovations and its implementation in production as soon as possible at the present stage are presented. The evaluation of the risks of economic development due to the crisis is presented. The issues of import substitution are considered. The analysis of the role of state and governments in the region to create conditions for import substitution is given. The main directions of development in the regional and the state economic policy in modern conditions are allocated. The financing options for innovative development are traced. The development plan for the production by import substitution by the example of a particular production is considered. The analysis of the existing problems in the economy is given.